Soil quality and fertility in vineyards of Kilis province of Turkey, the northwest of “fertile crescent” - Gokcen, Ibrahim Samet; Kuzucu, Meryem (Emirates Journal of Food and Agriculture, 2023)
This study was carried out in the vineyards in the Kilis province, where the cultivation of the “Horoz Karası” grape variety, which is also known as “Kilis Karası”, occurs. In the study, 10 vineyards were sampled from the central villages of Kilis, Kocabeyli, Gülbaba, Çerçili, Hisar, and Saatli. Physical and chemical analyses were performed on the soil samples taken from these pre-identified vineyards, and the nutritional status of 50 vineyards was examined. In the vineyards included and analyzed in this study, it was determined that the soils were too calcareous between 15.18-45.46%, the pH was slightly alkaline with pH values between 7.2-8.2, the phosphorus content was generally low between 0.57-10.63 kg/da, the potassium content was between 35.12-145.40 kg/da, and the organic matter was found to be insufficient with values between 0.64-2.12%. It was also determined that the vineyards included in this study had a clay loam structure, and that the soils of our province were suitable for viticulture despite the limited nutrients in the soil. The grape producers of our province do not fertilize the vineyards, so they need to add the nutrients needed in the vineyards through fertilization by conducting soil analyses in order to determine which nutrients are lacking, so that the production of crops can continue efficiently. Keywords: Kilis Karası; Nutrients; Physical and Chemical Properties of the Soil; Viticulture